Student perceptions about university security: The case of the National University of Costa Rica - Alfaro Salas, Marly Yisette (2020)
This work seeks to establish a baseline of the perception of safety of the student sector at the National University of Costa Rica. It works with a sample of n = 954 cases of the Omar Dengo Campus and the Benjamín Núñez Campus. We used our own development with 94-item Likert staggering and Cronbach’s alpha of .650. There are security threats of a political and cultural nature that are expressed in deepignorance of the matter, lack of a communication relationship between the security officer of the institution and the student sector and a low legitimacy of the officials who work in that field. It is concluded that the university has an important window of opportunity to be an integral university security manager inconjunction with other local actors such as communities and businesses.